Romiplostim for therapy‐related thrombocytopenia in pediatric malignancies. Issue 8 (2nd February 2017) - Jacobson, Amanda E.; Shah, Nilay; Setty, Bhuvana A.
Abstract: Therapy‐related thrombocytopenia (TRT), due to chemotherapy and/or radiation therapy, is common with pediatric cancer treatments, and it can result in dose reductions and therapy delays. Romiplostim, a thrombopoietin mimetic, is efficacious as a second‐line treatment for immune thrombocytopenia in children and for TRT in adult cancer patients. However, there are no data for its use for TRT in children. We report a case series of five children treated for solid tumors where romiplostim was used without adverse effects to successfully resolve and prevent therapy‐limiting refractory TRT. Prospective studies on this use of romiplostim are warranted.